PENGGUNAAN AIR SUSU SAPI YANG KAYA ASAM LEMAK LINOLEAT TERKOJUGASI SEBAGAI UPAYA UNTUK KENDALI METABOLIK(STUDI KASUS PADA PENDERITA DISLIPIDEMIA) - Suhartati, F.M.; Mulyanto, Djoko (Prosiding, 2012)
A study that aims to produce milk rich in conjugated linoleic acids and testing the milk for metabolic control has been implemented. As a material for producing milk are 5 female dairy cattle production. Cow feed consists of grass and concentrate with a ratio of 60:40. The method used is the pseudo eksperimental and the design was completely randomized design. The treatments tested, namely P1 = patients with dyslipidemia who were given simvastatin 10 mg / person / day, P 2 = patients with dyslipidemia who were given simvastatin 10 mg / person / day, and drinking dairy milk 300 ml / person / day, P3 = Patients dyslipidemia that drinking dairy milk 300 ml / day, P4 = normal cholesterol levels, drinking dairy milk 300 ml / day, P5 = normal cholesterol levels, without simvastatin and without drinking milk (as a negative control). Each treatment was repeated 6 times, so there were 30 respondents. As the respondent is a university lecturer and a female employee of General Sudirman, and SMA Veteran teachers, aged 40-60 years, who had suffered from dyslipidemia and non dyslipidemia. Before and after given treatment, respondents have blood drawn, and then measured the content of trigiserida, total cholesterol, LDL-cholesterol, HDL-cholesterol. Administration of simvastatin and milk implemented for a month. Data were analyzed using analysis of variance followed by orthogonal contrast test (Steel and Torrie, 1993). Based on these results it can be concluded that the respondents as negative control, has increased total cholesterol, triglycerides and LDLcholesterol and decreased HD-cholesterol. Consuming dairy milk 300 ml / person / day in combination with simvastatin 10 mg / person / day can lower-cholesterol, triglycerides, LDL and increase HDL-cholesterol. For patients with dyslipidemia, consume dairy milk 300 ml / person / day can lower LDL cholesterol and triglycerides and increases HDL-cholesterol. In an effort to reduce total cholesterol, triglycerides, LDL-cholesterol and increasing HDLcholesterol, patients with dyslipidemia early to do with the consumption of milk rich in conjugated linoleic fatty acids 300 ml / person / day and 10 mg simvastatin / person / day.